Psychobabble : exploding the myths of the self-help generation - Briers, Stephen, 1965- (Pearson, 2012)
Exposing the self-help myths that make us all more miserable. This is what your psychologist would really tell you-if he thought you could handle it! This is the kick up the backside the self-help genre needs: an intelligent, provocative and thought-provoking expose of the modern myths that we're told make us happier, but in reality screw us up. Clinical psychologist, Dr Stephen Briers shines a light into the dark corners of self-help and explodes the myths, false hopes, quack philosophies and unrealistic expectations it routinely advocates. It is a refreshing antidote to the `same o.